2018
DOI: 10.1111/mam.12114
|View full text |Cite
|
Sign up to set email alerts
|

Roosting ecology of Stenodermatinae bats (Phyllostomidae): evolution of foliage roosting and correlated phenotypes

Abstract: 1.Roosting ecology has probably shaped several aspects of bat evolution. Although Phyllostomidae species are known to use more types of roosts than any other chiropteran lineage, foliage roosting is almost entirely restricted to the frugivorous members of the subfamily Stenodermatinae. There are relatively few studies on the roosting ecology of stenodermatines other than leaf tent users, and there have been few attempts to reconstruct the evolution of the peculiar foliage-roosting habits of these fruit bats. 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
28
2
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 106 publications
1
28
2
5
Order By: Relevance
“…This contrasts with the recent review of Garbino and Tavares (), who concluded that the common ancestor of Stenodermatinae bats most probably roosted in tents. This discordance may be due to the difference in sample size, as Garbino and Tavares () study included 43 species of Stenodermatinae bats, about 40% less than ours, but also to the absence of species out of Stenodermatinae in our study. As we do not have any hypothesis that could predict an effect of yellow skin coloration on the occurrence of tent‐roosting, a role of tent‐roosting as a driver of skin coloration should be considered as the most likely explanation.…”
Section: Discussioncontrasting
confidence: 81%
“…This contrasts with the recent review of Garbino and Tavares (), who concluded that the common ancestor of Stenodermatinae bats most probably roosted in tents. This discordance may be due to the difference in sample size, as Garbino and Tavares () study included 43 species of Stenodermatinae bats, about 40% less than ours, but also to the absence of species out of Stenodermatinae in our study. As we do not have any hypothesis that could predict an effect of yellow skin coloration on the occurrence of tent‐roosting, a role of tent‐roosting as a driver of skin coloration should be considered as the most likely explanation.…”
Section: Discussioncontrasting
confidence: 81%
“…They argue that roosting ecology may be understood as a complex interaction of both biotic and abiotic variables, and roosting strategies may be directly influenced by the distribution and availability of food resources, among other things (Kunz and Lumsden ). Previous works have demonstrated that traits associated with roosting ecology might explain some morphological variation seen in phyllostomids (Garbino and Tavares ; Santana et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…), and living species have been highly successful in exploiting an array of roosting environments (Kunz and Lumsden ; Voss et al. ; Garbino and Tavares ) and food resources (Giannini and Kalko ). Their feeding strategies are exceptionally diverse among mammals, including insects, vertebrates, fruit, pollen, nectar, young leaves, and even blood (Ferrarezi and Gimenez ; Freeman ; Wetterer et al.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Artibeus and Sturnira are two genera of bats (Phyllostomidae, Stenodermatinae) that use hollow trees as main roosting sites, whereas most other stenodermatine bats roost in foliage or leaf tents (Evelyn & Stiles, ; Garbino & Tavares, ; Patterson et al., ). As a consequence, species of three genera of bat flies parasitize these two host genera.…”
Section: Discussionmentioning
confidence: 99%